Energy-saving effect of utilizing recirculated air in electric vehicle air conditioning system. (June 2019) - Pan, Leyan; Liu, Cichong; Zhang, Ziqi; Wang, Tianying; Shi, Junye; Chen, Jiangping
Highlights: Air conditioning load reduction strategy in vehicles using recirculated air is provided. Utilizing the recirculated air can extent the annual driving range by 11−30%. Energy saving of heat pump heating in electric vehicle air conditioning is provided. Abstract: The stock of electric vehicle is booming recently. However, the range of the electric vehicle is still a main barrier in its adoption. Air conditioning system is the second largest energy consumption device on vehicle, which will cause significant range reduction during operation. In this paper, the energy-saving effect of utilizing the recirculated air in air conditioning system is evaluated. The outside air ventilation rate based on CO2 limits and windshield anti-fog requirements are calculated, and the energy-saving effect of this strategy in 30 cities across China is evaluated using an annual energy consumption model. It is found that utilizing the recirculated air can save 14–46% heating energy when using PTC heater, and 33–57% heating energy in heat pump AC system. Throughout a year, utilizing the recirculated air can extend the driving range by 11–30%. Graphical abstract: Image, graphical abstract